Circulating tumor DNA in cholangiocarcinoma: current clinical applications and future perspectives - Wang, Yi; Li, Yike; Liang, Zhong; Zhang, Yuqiao; Li, Tong; Tian, Chenjun; Zhao, Jinyu; Jin, Boru; Cao, Jie; Lin, Yanyan (Frontiers in Cell and Developmental Biology, 2025)
Cholangiocarcinoma is a highly heterogeneous malignant tumor, including intrahepatic cholangiocarcinoma, hepatoportal cholangiocarcinoma and distal cholangiocarcinoma. Its incidence is increasing worldwide and currently accounts for approximately 15% of all primary liver cancers and 3% of all gastrointestinal malignancies. There is a lack of early diagnostic methods for cholangiocarcinoma, and the overall treatment effect is poor, with a 5-year survival rate of less than 25%. New biomarkers are urgently needed in clinical practice to improve the current diagnosis and treatment status. Circulating tumor DNA (ctDNA) is DNA fragments released by tumor cells, which can show tumor-specific gene mutations (such as IDH1/2, FGFR2 fusion) and epigenetic modifications (such as abnormal methylation). With the rapid development of tumor liquid biopsy technology, ctDNA has been gradually applied in solid tumors such as lung cancer and colorectal cancer due to its high sensitivity and dynamic monitoring capabilities. This review systematically introduces ctDNA technology and its progress in early screening, early diagnosis, treatment response, and prognosis monitoring of cholangiocarcinoma. In addition, this review also summarizes the challenges and limitations of current ctDNA technology and analyzes future hot research directions.